Family’s Coping Strategies in the COVID-19 Pandemic: Systematic Literature Review - Annisa Puti Kusnadi; Hanny Mentari Putri; Edwin Rosario Riyantono; Ika Febrian Kristiana (International Journal Labs, 2022)
The COVID 19 pandemic has brought many changes to families and caused various problems related to mental health, especially stress. This study aims to see family’s coping strategies in dealing with the challenges of the COVID-19 situation. The method used is a systematic literature review using the 2015 PRISMA guideline. This study uses articles obtained from the Scopus, Proquest, ScienceDirect, and Springerlink databases. The article search method was carried out by entering the keywords